2012
DOI: 10.5771/0949-6181-2012-4-464
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of transnational clusters: Evidence from the Slovak automotive industry

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Most studies found no further spillover linkages to other firms, except for those who received the original investment (e.g. He & Maskus, 2012;Aitken & Harrison, 1999;Cho et al, 2005;Konings, 2001;Motohashi et al, 2010;Zámborský, 2012). Aitken et al (1999), for example, found no evidence that domestic firms benefit from FDI spillovers in Venezuela.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies found no further spillover linkages to other firms, except for those who received the original investment (e.g. He & Maskus, 2012;Aitken & Harrison, 1999;Cho et al, 2005;Konings, 2001;Motohashi et al, 2010;Zámborský, 2012). Aitken et al (1999), for example, found no evidence that domestic firms benefit from FDI spillovers in Venezuela.…”
Section: Introductionmentioning
confidence: 99%
“…Srholec (2006) found that R&D intensity of local electronics firms in the Czech Republic was higher than R&D intensity of foreign entrants to the industry. Conversely, leading foreign investors such as PSA Peugeot Citroën in the Slovak car industry brought their most modern production technologies to their Slovakian plants, with PSA productivity levels in Slovakia surpassing those in firm's other locations (Zámborský 2012b). Although the technologies used by PSA in Slovakia were not developed there, Slovaks' qualifications and knowledge has allowed them to absorb foreign know-how.…”
Section: Discussionmentioning
confidence: 98%
“…Clusters in the growth phase have a larger number of employees and ventures; the only decrease tends to be in knowledge heterogeneity compared to the emergence stage (Mahroum and Al-Saleh, 2016; Zámborský, 2012). The decrease in the knowledge heterogeneity is associated with the emergence of a dominant technological design, which offers clear benefits by adopting technical routines (Menzel and Fornahl, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%